Implementation of Policies on Educational Curricula in Schools - Rawdia Tuzahara; Shifa Azzahra; Abdul Ganif Herlambang; Azzahra Kamila Cahyani Masdar (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to provide an in-depth description of the implementation of curriculum policy in an Islamic elementary school (madrasah ibtidaiyah). The focus of the research includes the stages of planning, implementation, assessment, and the challenges faced in applying the curriculum. The research methods used were direct classroom observation, interviews with the head of the madrasah and classroom or subject teachers, as well as document analysis of curriculum materials such as the KTSP, annual programs, semester programs, syllabi, and lesson plans (RPP). The findings indicate that curriculum planning was carried out systematically in accordance with regulations from the Ministry of Religious Affairs and the Ministry of Education, through the development of curriculum documents involving teachers in KKG forums and school workshops. In the implementation stage, teaching referred to the 2013 Curriculum and began adapting the Merdeka Curriculum, especially in lower grades, by applying differentiated instruction and project-based learning to strengthen the Profile of Pancasila Students. Assessment was conducted comprehensively, covering attitudes, knowledge, and skills using various assessment instruments. The study also identified several challenges, including the need to improve teacher competence in developing teaching materials based on the Merdeka Curriculum and the limited availability of facilities to support thematic and innovative project-based learning.